Harnessing Social Media for Religious Peacebuilding: Faith in the Digital Age - Jalando-on, Francis Neil Gico (Pascasarjana IAIN Pontianak, 2025)
This study explores social media’s potential as a tool for religious peacebuilding, focusing on its capacity to foster harmony through faith-based values in a digitally connected world. With 5.24 billion users globally and 90.8 million in the Philippines, where religion shapes cultural identity, social media offers unprecedented opportunities to connect faith communities, amplify sacred narratives, mobilize action, and educate for peace. Drawing on global and Philippine examples, we examine how platforms like Facebook, X, and TikTok channel religious teachings to promote reconciliation, while addressing challenges like polarization, misinformation, hostility, and slacktivism. Historical narratives, including Hong Kong’s Yellow Umbrella Movement and the Philippines’ #FaithForTruth campaign, illustrate faith’s role in digital peacebuilding. Eight strategies, grounded in religious ethics, propose harnessing social media’s strengths: global reach, real-time engagement, education, and community-building to counter division. By embedding values like forgiveness and truth, religion transforms social media into a sacred space for peace, offering a model for conflict-affected regions like Mindanao.